(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Foeniculum vulgare Mill, commonly referred to as fennel, was used for a wide range of diseases in traditional medicine. The plant is native to the Mediterranean region and Southern Europe. This contains basic essential oil and fatty acids. Due to its volatile and non-volatile chemicals, fennel has many biological activities. The oil components were analyzed using gas chromatography-mass spectrometry (GC-MS). The analysis of seed extracts showed the presence of 12 compounds of essential oil and 10 compounds of fixed oil. The antimicrobial function of F. vulgare oil was evaluated via the diffusion assay against six standard human pathogens (S. aureus, B. cereus, E. coli, S. epidermidis, and P. vulgaris), along with the minimum inhibitory concentration (MIC) technique. Fennel oil demonstrated a broad antibacterial spectrum (Gram-negative and Gram-positive bacteria) by inhibition against the six types of bacteria. Fennel oil also showed excellent antioxidant activity compared with the reference compound. Consequently, fennel oil could be an origin for pharmaceutical substances necessary for the development of new antimicrobial and therapeutic agents and antioxidants.